The effect of 2, 4-D (2, 4-dichlorophenoxyacetic acid) and glyphosate (N-phosphonomethyl glycine) toxicity on stingless bee, Trigona itama using direct spray and bioassays methods - Md Amin, Mohd Hairul Fazli (2018)
Stingless bee (Trigona itama) is the largest group of eusocial insects on earth, simply called as meliponines. The most common genus of the stingless bees are Melipona and Trigona. Stingless bees are the main pollinators of many flowering plants in tropics. Among various honey in Malaysia, the honey produced from Trigona contains high level of potassium, magnesium, iron and zinc. However, because this insect used as a pollinator, there are some issues that relate to the herbicide uses towards the pollinator insect especially bees. Herbicides are the most widely used pesticide in agriculture worldwide both in terms of the volumes used and the areas treated. Although it is used to killed weeds, however, it could killed stingless bees directly or indirectly. The objective of this study is to determine the mortality and toxicity level of two most commonly used herbicide on stingless bee. This experiment were conducted at two different places which are the Field 10, Faculty of Agriculture, Universiti Putra Malaysia and Laboratory C, Department of Plant Protection, Faculty of Agriculture, UPM. Direct spray method and filter paper bioassay method were used to determine the mortality and toxicity level of herbicides on stingless bee. For direct spray method, a recommendation rate of 2, 4-D Amine and Glyphosate were sprayed directly to stingless bee. The second experiment is filter paper bioassay method, where four concentrations of 2, 4-D amine and Glyphosate and were tested to find the LC50 value of the herbicides. Both experiments were replicated four times with 10 stingless bees in each replication. On direct spray method shows that these herbicides does have toxicity effect on stingless bee as after 24 hour, all stingless bee died in both treatments. The toxicity study shown 2, 4-D herbicide are more toxic than Glyphosate. LC50 Value of 2, 4-D amine for 24 and 48 hr are 296.153 ppm and 137.128 ppm respectively while Glyphosate in 24 and 48 hour are 483.509 ppm and 315.423 ppm respectively. Thus 2, 4-D Amine has higher toxicity level compare to Glyphosate.